Building criteria to evaluate qualitative research papers: a tool for peer reviewers - Costa, António Pedro (2019)
Objective: To present some criteria, many of which were created in the form of a checklist of items to be considered throughout the review process. Furthermore, we present a study whose main objective was to build (and validate) a review instrument by specialists that is clear, comprehensive, concise and consistent with the highest standards of excellence. Method: We use a survey to collect data (123 answers). To analyze the open answers we use the technique of content analysis through the Qualitative Data Analysis Software. Results: Besides the creation of new criteria with a focus on methodological dimensions based on 12 items, the involvement of the Ibero-American Congress on Qualitative Research scientific committee in the validation of this instrument. Conclusion: This option, in line with the others described, will allow to implement improvements to the editions of the events using the Qualitative Research Evaluation Tool in 2018.